On Methodology In The Study Of Management And Organization - Hicks, Herbert G.; Goronzy, Friedhelm (Academy of Management Journal, 1967)
This paper describes, analyzes, and classifies methodologies that have been employed in developing certain management and organization theories. The authors also examine the effects of methodology and value systems on the construction, evaluation, and utilization of theories for management and organization.